2020
DOI: 10.3389/fcell.2020.599472
|View full text |Cite
|
Sign up to set email alerts
|

PHF6 Expression Levels Impact Human Hematopoietic Stem Cell Differentiation

Abstract: Transcriptional control of hematopoiesis involves complex regulatory networks and functional perturbations in one of these components often results in malignancies. Loss-of-function mutations in PHF6 , encoding a presumed epigenetic regulator, have been primarily described in T cell acute lymphoblastic leukemia (T-ALL) and the first insights into its function in normal hematopoiesis only recently emerged from mouse modeling experiments. Here, we investigated the role of PHF6 in human blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 61 publications
3
13
0
Order By: Relevance
“…Supporting a fundamental role for PHF6 in general development, PHF6-homozygous knockout mice die perinatally (9). However, scientists have also developed various knockout models in mice to explore the role of PHF6 in hematopoiesis (8,(10)(11)(12)(13). McRae et al showed that germline deletion of murine PHF6 is lethal in males whereas heterozygous females survived to adulthood (10).…”
Section: Function Of Phf6mentioning
confidence: 99%
See 3 more Smart Citations
“…Supporting a fundamental role for PHF6 in general development, PHF6-homozygous knockout mice die perinatally (9). However, scientists have also developed various knockout models in mice to explore the role of PHF6 in hematopoiesis (8,(10)(11)(12)(13). McRae et al showed that germline deletion of murine PHF6 is lethal in males whereas heterozygous females survived to adulthood (10).…”
Section: Function Of Phf6mentioning
confidence: 99%
“…Supporting a fundamental role for PHF6 in general development, PHF6- homozygous knockout mice die perinatally ( 9 ). However, scientists have also developed various knockout models in mice to explore the role of PHF 6 in hematopoiesis ( 8 , 10 13 ). McRae et al.…”
Section: Function Of Phf6mentioning
confidence: 99%
See 2 more Smart Citations
“…HSPCs from the patient with MDS showed an increased levels of transcription factors involved in the prevention of erythropoiesis such as JUN, YBX1, LMO2, and LYL1 (36,37). On the other hand, the expression of genes such as SLC25A6, EPSTI1 and PHF6, which play a prominent role in the promotion of erythroid differentiation, failed to raise in HSPCs from this patient (38,39). Despite these changes, we observed that essential drivers of erythropoiesis (GATA1, and KLF1) as well as erythroid specific markers (AHSP, CA1, and HBB) followed trends similar to those of healthy HSPCs, which is in agreement with the apparently normal progression of differentiation at the progenitor stages.…”
Section: Scrna-seq Analysis Of Mds and Aml Specimens Reveals Molecular Lesions Affecting Normal Hematopoietic Differentiationmentioning
confidence: 71%